Analysing Mrs Everything: A Novel through the Lens of Embodied Sexual Practice Perspective - Aleena Hussain; Amna Khalil (Journal of Research in Humanities, 2022)
Regardless of the era, women are faced with the threat of rape constantly. The novel Mrs Everything: A Novel (2019) by Jennifer Weiner was explored under the lens of the Embodied Sexual Practice Perspective theory presented by Ann J. Cahill to highlight the dismal consequences of rape or the threat of rape incidents. The research investigates the molestation of Bethie by Uncle Melvin, the effects of rape on Bethie, and analyzes the sexual assault of Lila by her boss. The characters of Bethie Kaufman and Lila Braverman who experienced sexual abuse were subjected to sexual shame, victim-blaming, rape trauma, and fragmentation of self and subjectivity. This paper suggests the revision of laws and the spread of awareness to change societal norms to eradicate the threat of rape and the actions that allow derivatization so that womanly subjectivity and aspirations are allowed equal freedom.